2011
DOI: 10.1051/0004-6361/201118189
|View full text |Cite
|
Sign up to set email alerts
|

First detection of hydrogen isocyanide (HNC) in Titan’s atmosphere

Abstract: We report on the first identification of hydrogen isocyanide (HNC) in Titan's atmosphere, from observations using the HIFI instrument on the Herschel Space Observatory. An emission line from the HNC J = 6 → 5 rotational transition at 543.897 GHz was measured in Titan on June 14 and December 31, 2010. Radiative transfer modeling indicates that the bulk of HNC is located above 400 km, with a column density in the range (0.6−1.5) × 10 13 cm −2 , but the observations cannot establish its vertical profile. In parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 43 publications
2
52
1
Order By: Relevance
“…2 and are compared with our model. The column density we obtain is 3.4 × 10 13 cm −2 above 500 km whereas the value derived by Moreno et al (2011) at this altitude is 1.2 × 10 13 cm −2 (about 3 times lower). We will see in the following that this discrepancy can be simply explained by our poor knowledge of some key reactions.…”
Section: Hnc Observationscontrasting
confidence: 72%
See 4 more Smart Citations
“…2 and are compared with our model. The column density we obtain is 3.4 × 10 13 cm −2 above 500 km whereas the value derived by Moreno et al (2011) at this altitude is 1.2 × 10 13 cm −2 (about 3 times lower). We will see in the following that this discrepancy can be simply explained by our poor knowledge of some key reactions.…”
Section: Hnc Observationscontrasting
confidence: 72%
“…Following the prediction of Petrie (2001), Moreno et al (2011) concluded that a purely ionospheric source may be quantitatively viable for HNC, provided that the protonation rates are not too high. Here we show that a purely neutral source is efficient enough to produce HNC and HCN in the upper atmosphere of Titan in agreement with current observations.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations